Analgesic Activities of Ethanolic and Methanolic Extract of Ganitri Leaves (Elaeocarpus ganitrus Roxb): In vivo study - Naelaz Zukhruf Wakhidatul Kiromah; Chondrosuro Miyarso; Yayu Krisdiyanti (Universitas Muhammadiyah Yogyakarta, 2021)
Pain is a feeling of discomfort caused by intense or destructive stimuli, which can affect your daily routine if left untreated. Pain can be treated with an analgesic. One of the plants that are considered to have analgesic effects is the leaves of the ganitri. This research aims to determine ethanol and methanol extracts' impact on decreasing analgesic activity and percent protection. The study began with collecting and processing the leaves of the ganitri into the ethanol and methanol extracts using the maceration method. The research was continued with in vivo analgesic activity testing of 24 mice induced by pain using 1% acetic acid. The induced mice were divided into eight treatment groups, where the mice in the first group served as a negative control group. In that group, they were given CMC at a dose of 0.5%. The second group was positive control, given mefenamic acid at a dose of 500 mg/kg BW. In contrast, the third until eighth groups were given ethanol and methanolic extracts of the ganitri leaves with consecutive doses of 100 mg/kg BW, 200 mg/kg BW dan 400 mg/kg BW. Parameters measuring the effectiveness of the extracts used in this study included the amount of stretching, the percentage of analgesic power, and analgesic effectiveness. The results showed that the ethanolic and methanolic extract had the highest percentage of analgesic power at 400 mg/Kg BW amounted to 91,3% and 88,3%. Furthermore, based on the statistical analysis results using ANOVA, it was found that the ethanol and methanolic extracts of the leaves of the ganitri dosage of 400 mg/Kg BW had analgesic activity close to 500 mg/kg BW of mefenamic acid.